Improved definition of growing pains: A common familial primary pain disorder of early childhood - G. David Champion; Minh Bui; Sara Sarraf; Theresa J. Donnelly; Aneeka N Bott; Shuxiang Goh; Tiina Jaaniste; John Hopper (Wiley, 2022)
Abstract Background Commonly applied diagnostic criteria for growing pains (GP) have evolved without determination by an authoritative representative body. GP and restless legs syndrome (RLS) share anatomical, distributional, temporal, and other clinical features and are associated in individuals over time, in families, and in population samples. In this study, we tested the hypothesis that GP, diagnosed by widely used criteria, is confounded by cases of painful restless legs syndrome (RLS‐Painful). Methods A twin family study of genetic influence and associations of GP using questionnaires was administered by Twins Research Australia. Twins (3-18 years; monozygous 503, dizygous 513), their oldest siblings, mothers, and fathers were randomly selected from the twin registry. Family members completed the questionnaires assessing lifetime prevalence of GP by commonly applied criteria and covariates including the history of iron deficiency and pediatric pain disorders. A GP‐Specific phenotype was defined as GP without urge to move the legs. We determined similarities in twin pairs for the GP and GP‐Specific phenotypes, family associations, and estimated familial and individual‐specific associations for each phenotype. Results Lifetime prevalence was one‐third lower for GP‐Specific than for GP among the twin and family members. Monozygous twin pairs were more similar than dizygous twin pairs for GP and for the derived GP‐Specific phenotype by three methods, consistent with genetic influence. There were familial associations, but the essential evidence for genetic influence was the twin‐cotwin data. GP was associated, in multivariable analyses, with migraine, headaches, recurrent abdominal pain, and iron deficiency, while GP‐Specific associations were limited to migraine and headaches. Conclusions GP is hybrid, one‐third of cases having symptoms and associations of RLS, necessarily RLS‐Painful. GP‐Specific (without symptoms and associations of RLS) could have a genetic etiology. We propose new criteria to facilitate etiological and therapeutic research.